2019
DOI: 10.1088/1755-1315/370/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Habitat characteristics and distribution of flyingfish in Fak-Fak and surrounding waters

Abstract: In Indonesia, flyingfish are abundant and distributed in Makassar Strait, Flores Sea, Banda Sea, Sulawesi Sea, Maluku Sea, Arafura, Northern Sea of Papua, and Halmahera. The aims of this study were to analyse and describe the characteristics of flyingfish habitat, based on oceanographic conditions and eggs catches, and to visualize the variability in spatial and temporal patterns of predicted potential spawning grounds. The research was conducted in Fak-Fak and adjacent seas in the Indonesian Fisheries Area WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…This indicates that the peak of flying fish egg captures in the waters of the Aru Islands is in July to August, with the presence of eggs in these waters for five months (May-September). Similar trends have been observed in flying fish resources in the waters Kei Islands [40], the Seram Sea [41,42], East Seram to Fakfak [43], and waters near Timor Leste [44].…”
Section: The Results Include Single Mixed and Double Seat Capturessupporting
confidence: 77%
“…This indicates that the peak of flying fish egg captures in the waters of the Aru Islands is in July to August, with the presence of eggs in these waters for five months (May-September). Similar trends have been observed in flying fish resources in the waters Kei Islands [40], the Seram Sea [41,42], East Seram to Fakfak [43], and waters near Timor Leste [44].…”
Section: The Results Include Single Mixed and Double Seat Capturessupporting
confidence: 77%
“…Chlorophyll-a concentration, sea surface temperature, waves, depth and current speed affect the presence of flying fish. Flying fish are found in the chlorophyll-a range of 0.25 -0.70 mg/m³, sea surface temperatures of 27.5-29.5°C, current speeds of 25.0 -42.5 m/s (Zainuddin 2011) and waves between 0.70 -1.60 m (Boli et al 2019). A survey conducted by Churnside et al 2017 found schools of flying fish at an average depth of 5.27 m at night and 4.61 m during the day.…”
Section: Flying Fish Distributionmentioning
confidence: 99%
“…The abundance of flying fish is influenced by oceanographic conditions in the form of sea surface temperature, chlorophyll, currents and waves (Boli et al 2019;Zainuddin 2011). In addition, the abundance and distribution of flying fish is also strongly influenced by the presence of upwelling in the waters.…”
Section: Production and Fishing Gearmentioning
confidence: 99%
“…Flying fish tend to look for spawning grounds that have oceanographic characteristics characterized by low SST and high chlorophyll-a (Boli et al, 2019). Flying fish will also choose spawning grounds with clear waters, lots of floating objects, and the presence of Sargassum seaweed.…”
Section: The Relationship Between Sst and Chlorophyll-a With The Dist...mentioning
confidence: 99%